The Ethics of Speculation - Angel, James Joseph (Journal of business ethics, 2009)
Recently there has been an outpouring of consumer frustration over rising food and energy prices. Many politicians railed against “speculators” who allegedly drove up the prices of key necessities. Is speculation unethical? This article reviews the traditional arguments against speculation. Many of the standard criticisms confuse speculation with gambling. In much the same way as ethicists now draw distinctions between usury and normal business interest, we draw a distinction between socially useful speculation and gambling. Gambling involves taking on risk with no plausible expectation of making a profit. Gambling may provide entertainment value to some people, but like other addictive activities causes grave harm to a subset of users. Speculation involves taking on a business risk with a plausible expectation that a profit will result. Speculators provide an important risk bearing service by taking on risks that others do not want. They help markets to function better by helping to incorporate information into prices as well as providing liquidity. Speculators may actually reduce shortages by causing quicker price increases that motivate producers to increase production and consumers to conserve. But even socially useful speculation may have an ethical dark side. Does such speculation cause damage by adding excess volatility to prices? Speculators may contribute to price bubbles. At what point does legitimate speculation become odious “price gouging?” We also draw an ethical distinction between speculation, which seeks to benefit from changing prices, and manipulation, actions taken to push prices away from their economically appropriate levels.